The scientific results in the biomedical investigations: an unresolved challenge - Nadina Travieso Ramos (Centro Provincial de Información de Ciencias Médicas, 2017)
The characteristics of the main types of scientific results that can be obtained during the development of the biomedical investigations are exposed in this work, taking into account the classification that divides them in theoretical and practical results.  Also the essential particularities of the concepts, conceptions, models and systems, as contributions to the knowledge are presented, besides other theoretical contributions, as the stages, the relationships and the levels or degrees of certain investigation objects.  As for the practical results; the methods, techniques, methodologies,  strategies and  material objects are determined, and  those corresponding to the normalization of the medical practice, as  algorithms and  protocols are highlighted.  With this methodological alternative it is sought to contribute to the improvement of the science management processes in the area of knowledge of the biomedical investigation.